Knowledge, perceptions and practices of selected barangay nutrition scholars from Pampanga on the Pinggang Pinoy® - Intal, Maria Verna Y.; Villarino, Casian Blanca (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
In 2015, the Department of Science and Technology - Food and Nutrition Research Institute (DOST-FNRI) developed the Pinggang Pinoy®. It is a visual food guide that uses a food plate model to encourage different population groups to consume the right quality and quantity of food on a per meal basis. This tool complements the use of the Daily Nutritional Guide (DNG) Pyramid, another tool developed by the DOST-FNRI. The Barangay nutrition scholars (BNS) are the among the most critical users of the Pinggang Pinoy®, being the primary channels in bringing health and nutrition awareness in the community. This study aimed to determine the knowledge, perceptions and practices of the BNS on the Pinggang Pinoy®. A total of one hundred thirty five (135) BNS were randomly selected from the nineteen (19) municipalities in Pampanga based on a set of inclusion criteria. Using developed, validated and pre-tested questionnaires, data on socio-economic-demographic characteristics; work background as well as knowledge, perceptions, and practices of the BNS on the Pinggang Pinoy® were collected. Descriptive statistics (mean, standard deviation, frequency, and percentage) were used in analyzing the socio-economic demographic characteristics, work background, knowledge, perception and practices scores of the BNS. Pearson and Spearman's Rho correlation test were used in determining the relationships of the variables. The study showed that the majority of the BNS were not knowledgeable (88.1%) but have positive perceptions (99.3%) about the Pinggang Pinoy® as a nutrition education tool. Almost all (97%) of the BNS had poor practices in terms of using the P inggang Pinoy® as a nutritin education tool. Additionally, there were significant relationships between perception and total number of trainings (p=.01); practices and length of service (p=.01); practice and total number of attended trainings (p=.01); and practices and total minutes of attended trainings (p=.05). Also, a significant relationship (p=.01) was seen between knowledge and perception. There is a need to improve the BNS' knowledge and practices on the Pinggang Pinoy®. Good qualtiy and standardized trainings, seminars and lectures could be conducted to increase the knowledge and skills on the use of Pinggang Pinoy® as a nutrition education tool. Continued refinement of communication approaches for the implementation of Pinggang Pinoy® at the grassroots should be done to improve its usefulness and effe
Thesis Classification
Thesis
Includes bibliographical references and appendices.
Keywords: Nutrition -- Philippines